2016
DOI: 10.1111/ped.12925
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal vitamin A supplementation associated with adverse child behavior at 3 years in a prospective birth cohort in Japan

Abstract: Intake of supplemental vitamin A prior to and/or during pregnancy may worsen child behavior at 3 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The VAS group also had poorer weight gain and smaller lower arm circumference. A prospective birth cohort study in Japan showed that supplemental vitamin A intake prior to and/or during pregnancy was significantly associated with disturbed behavior at three years of age, after adjustment for numerous factors (age, number of deliveries, infertility treatment, consumption of fast food, smoking status, maternal and paternal education and income, gestational age at birth, infant’s weight, height, head circumference and body circumference, and the State-Trait Anxiety Inventory at age three) [177].…”
Section: Could Other Risk Factors Be Involved?mentioning
confidence: 99%
“…The VAS group also had poorer weight gain and smaller lower arm circumference. A prospective birth cohort study in Japan showed that supplemental vitamin A intake prior to and/or during pregnancy was significantly associated with disturbed behavior at three years of age, after adjustment for numerous factors (age, number of deliveries, infertility treatment, consumption of fast food, smoking status, maternal and paternal education and income, gestational age at birth, infant’s weight, height, head circumference and body circumference, and the State-Trait Anxiety Inventory at age three) [177].…”
Section: Could Other Risk Factors Be Involved?mentioning
confidence: 99%
“…Numerous studies suggest that there may be beneficial effects of maternal diet in pregnancy on child neurodevelopment, albeit, again with mixed results ( Borge et al, 2017 ). Intakes of antioxidants, n-3 fatty acids, and foods rich in these nutrients have been associated with child developmental outcomes with inconsistent findings ( Guxens et al, 2012 ; Brew et al, 2015 ; Delgado-Noguera et al, 2015 ; Emmett et al, 2015 ; Bolduc et al, 2016 ; Catena et al, 2016 ; Ishikawa et al, 2016 ; Julvez et al, 2016 ; Bruce-Keller et al, 2017 ; Lipton et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, excess VA intake in pregnancy has also been associated with increased risk of birth defects ( 160 ). A birth cohort study in Japan found an association between prepregnancy or antenatal VA and β-carotene supplementation and worsened child behavior at 3 y of age ( 161 ).…”
Section: Resultsmentioning
confidence: 99%